2007
DOI: 10.2522/ptj.20060121
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective Evaluation of the AM-PAC-CAT in Outpatient Rehabilitation Settings

Abstract: Overall, the AM-PAC-CAT's Basic Mobility scale demonstrated excellent psychometric properties while the Daily Activity scale demonstrated less adequate psychometric properties when applied in this outpatient sample. The mean length of time to complete the Basic Mobility scale was 1.9 minutes, using, on average, 6.6 items per CAT session, and the mean length of time to complete the Daily Activity scale was 1.01 minutes, using on average, 6.8 items. BACKGROUND AND CONCLUSION: Overall, the findings are encouragin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
123
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 34 publications
5
123
0
Order By: Relevance
“…8,25,30,34,35,50,52 Therefore, multivariable statistical models tend to control the effect of risk adjustment variables in clinically logical ways.…”
Section: T T Conclusionmentioning
confidence: 99%
“…8,25,30,34,35,50,52 Therefore, multivariable statistical models tend to control the effect of risk adjustment variables in clinically logical ways.…”
Section: T T Conclusionmentioning
confidence: 99%
“…The eleven variables included for risk adjustment were intake FS, 10,22,24,33,44,46 intake pain intensity, [66][67][68] 44,47 and number of comorbid conditions. 10,21,45 These eleven variables were specifically selected for inclusion in our linear-regression models, because the previously cited studies demonstrated that each variable influenced FS or pain outcomes in predictive models.…”
Section: Risk Adjustment Factorsmentioning
confidence: 99%
“…30 With good precision, CAT scores are calculated at the item level, using up to 10 questions. 31,32 Item response theory/CAT methods allow the addition of new items into calibrated banks with replenishment calibrations studies. 33 CAT systems currently in use include the Patient Reported Outcomes Measurement Information System 34 and the osteoarthritis (OA) CAT systems ie OA-DISABILITY-CAT, OA-FUNCTION-CAT).…”
Section: Future Directions: Computer-adaptive Testing Systemsmentioning
confidence: 99%